Design and optimization of non-uniform 1 × 5 PLC splitter using orthogonal experimental method - Wang, Jirong; Zheng, Yu; Zou, Xinjie; Zhao, Yanbing; Liu, Jianzhe; Jiang, Xiang; Duan, Ji'an (Optics and laser technology, 2024)
•A non-uniform 1 × 5 PLC splitter with excellent performance is designed and manufactured.•The sensitivity of device performance to each structure size is discussed using orthogonal experimental method.•The performance of optical splitter oscillates with the increase of the length of narrow straight waveguide. The non-uniform planar lightwave circuit (PLC) splitter with one primary and multiple signal distribution function is one of the most crucial devices in Fiber-To-The-Room (FTTR) technology. Reducing the device loss and optimizing output uniformity are challenging obstacles during the design and optimization process of PLC splitters. In this paper, the design and optimization of a non-uniform 1 × 5 PLC splitter are carried out, and the device performance sensitivity analysis towards various structure dimensions was then determined using the orthogonal experimental method. The measurement results show that for an operating wavelength range from 1.27 μm to 1.63 μm, the insertion loss (IL) of the main channel is less than 1.25 dB. Whilst the IL, wavelength-dependent loss (WDL), and uniformity loss (UL) of channel 2 ∼ 5 are less than 14.06 dB, 0.18 dB, and 0.24 dB, respectively. The adopted design method has manifested convenient practicality and advanced efficiency and could considerably scale down the design and optimization cycle of PLC splitters.